Reduced Self‐Absorption of Quasi‐2D Perovskites and Their Application in Color Conversion Layers. Issue 1 (3rd November 2022) - Liu, Nian; Luo, Jiajun; Guo, Qingxun; Du, Peipei; Gao, Liang; Niu, Guangda; Song, Boxiang; Tang, Jiang
Abstract: Lead halide perovskites (LHPs) have recently demonstrated great potential for color conversion layers (CCLs) in backlight displays due to their ultrahigh color purity and high photoluminescence quantum yield. However, the severe self‐absorption effect of LHPs due to small Stokes shift restricts their optical conversion efficiency (OCE) as CCLs. Herein, quasi‐2D perovskites are exploited and the ultrafast energy transfer mechanism is introduced. Using this approach, CCLs Stokes shift is increased and its self‐absorption coefficient is reduced by nearly threefold (from 6.2 × 10 4 to 2.1 × 10 4 cm −1 ). Therefore, color conversion light‐emitting diodes based on quasi‐2D perovskites are demonstrated with an improved OCE of 30% and ideal working stability of 1% loss under blue light irradiation of 35 mW cm −2 indicating their great potential for application in backlight display. Abstract : The energy transfer mechanism in quasi‐2D perovskites is introduced to attenuate the self‐absorption effect in perovskites and the specific self‐absorption coefficient (α2 ) is reduced from 6.2 × 10 4 to 2.1 × 10 4 cm −1 . The obtained quasi‐2D perovskite further demonstrates the decent optical conversion efficiency and good blue light stability that are favorable for color conversion applications.